The Potential of Board Games in Cultural Institutions: The Case of the “Upper Silesian Pantheon” in Katowice - Szostek, Bartosz (Sensus Historiae, 2025)
This article examines the use of board games as an educational tool in cultural institutions, with a focus on the "Upper Silesian Pantheon" in Katowice. Board games enhance engagement, support cognitive and social skills, and make learning more interactive. The study highlights the educational value of the game Become a Pantheon Champion, which introduces participants to Upper Silesian history through active participation. The findings suggest that board games can effectively complement traditional learning methods in museums and cultural spaces.